Impaired left atrial systolic function and inter-atrial dyssynchrony may contribute to symptoms of heart failure with preserved left ventricular ejection fraction: A comprehensive assessment by echocardiography. (15th April 2018) - Liu, Shuang; Guan, Zhengyu; Zheng, Xianfeng; Meng, Pingping; Wang, Yonghuai; Li, Yang; Zhang, Yan; Yang, Jun; Jia, Dalin; Ma, Chunyan
Abstract: Aims: To assess LA diastolic and systolic function and atrial dyssynchrony in patients with heart failure with preserved ejection fraction (HFpEF) and to examine whether LA dysfunction and dyssynchrony account for the patients' symptoms of HFpEF. Methods: Fifty-five patients with HFpEF, 31 asymptomatic patients with left ventricular diastolic dysfunction (LVDD) and 33 healthy individuals were enrolled in the study. The LA active ejection fraction (LAAEF) was calculated. The peak atrial longitudinal systolic strain (PALS) and peak atrial contraction strain (PACS) were measured using speckle tracking echocardiography (STE). Atrial dyssynchrony including inter-atrial dyssynchrony, LA dyssynchrony and right atrial dyssynchrony were calculated by tissue Doppler imaging (TDI). Results: The PALS and PACS were deteriorated, whereas inter-atrial dyssynchrony was prolonged in patients with HFpEF (20.41 ± 7.41%, 10.83 ± 4.19%, 31 ± 15 ms, respectively) compared with the values obtained in asymptomatic LVDD patients (26.61 ± 6.30%, 13.23 ± 4.52%, 19 ± 12 ms, respectively) and those found in normal individuals (33.51 ± 6.74%, 14.17 ± 2.88%, 17 ± 12 ms, respectively) ( P < 0.05). However, PACS and inter-atrial dyssynchrony did not reach statistical significance between asymptomatic LVDD and normal individuals ( P > 0.05). Moreover, patients with deteriorated clinical symptoms (NYHA > II) presented worse LA systolic function and prolonged dyssynchrony compared with those with NYHA = II. Inter-atrial dyssynchrony and LAAEF are independently associated with worse NYHA functional classes in patients with HFpEF. Conclusions: LA diastolic and systolic function were significantly impaired, and inter-atrial dyssynchrony was prolonged in patients with HFpEF. Decreased LA systolic function and prolonged inter-atrial dyssynchrony were possibly associated with deteriorated clinical symptoms. Highlights: Left atrial functions were reduced in heart failure with preserved ejection fraction. Left atrial dyssynchrony was increased despite preserved ejection fraction. Impaired atrial dyssynchrony and function related to deteriorated clinical symptoms